BOTULINUN TOXIN A EFFECTS AND PHYSIOTHERAPY ON MUSCLE TONUS AND STRENGTH IN A SPASTIC DIPLEGIC CHILD (Fiep Bulletin - online, 2014)
The objective of this case study was analyze qualitatively the alterations of the tonus, force and joint amplitude of the lower limbs after application of the BTA. A seven years child of the male sex with spastic diplegy was selected for participate of the study. The child was submitted to two evaluations: before of the application of the BTA in gastrocnemius bilaterally and another one after four months. During these four months the child participated regularly of the physical therapy, three times weekly that consisted of kinesioterapy based in the Bobath Neurodevelopmental Concept. The study had qualitative character having like dependent variables: force, muscular tonus and the angular variation of the lower. The gait was evaluetad by means of the three cameras of 60Hz with acquisition and processing by the software QView and construction of the graphics by the QGait, with markers in lower limbs and pelvis. For the evaluation of the muscular tonus utilized itself to scale of Durigon & Piemonte (1993) and of the forces by means of the scale of Daniels & Worthingham (1987). The result showed that associated with the decrease of the tonus it was observed increased of force of the majority of the muscular groups evaluated. Concomitantly, it observed itself increase in the amplitude of movement of the hip, knee and ankle in the sagital plane. This indicates that the physical therapy program proposed associated to the application of the BTA resulted in the increase of force of the muscular groups evaluated.
Keywords: Botulinun Toxin A; Physiotherapy; Spastic Diplegic